1998
DOI: 10.1161/01.str.29.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Velocity in Acute Schizophrenic Patients

Abstract: Background and Purpose-The aim of this study was to determine whether acutely psychotic first-episode schizophrenics show an increased cerebral blood flow velocity and whether this condition is reversible on psychopathological improvement. Methods-In the first of two examinations, transcranial Doppler ultrasonography and assessment with the Positive and Negative Syndrome Scale (PANSS) were performed on 28 acutely psychotic, neuroleptically naive, first-episode schizophrenics. In the second examination, the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In few studies described in the literature, where TCD was performed without activation paradigms, authors found increased BFV in a sample of 28 and 20 patients with FEP compared to healthy subjects (Owega et al 1998, Lee et al 2008, or found no differences in BFV in a sample of 55 patients with schizophrenia and 15 patients with FEP in comparison to healthy controls (Lee et al 1999).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In few studies described in the literature, where TCD was performed without activation paradigms, authors found increased BFV in a sample of 28 and 20 patients with FEP compared to healthy subjects (Owega et al 1998, Lee et al 2008, or found no differences in BFV in a sample of 55 patients with schizophrenia and 15 patients with FEP in comparison to healthy controls (Lee et al 1999).…”
Section: Discussionmentioning
confidence: 92%
“…Some of these results were interpreted as results of cerebral hemodynamics in patients with schizophrenia and also with first episode psychosis, although results are inconsistent (Santra & Kumar 2014, Kanahara et al 2013, Tsujino et al 2011, Wake et al 2010, Molina et al 2005, Riehemann et al 2001, Hoptman & Antonius 2011. As well as with other techniques, many studies that included Transcranial Doppler (TCD) ultrasonography to measure cerebral blood flow velocity (BFV) and pulsatility in main intracranial arteries with excellent temporal resolution (Wintermark et al 2005), indicated that patients suffering from schizophrenia or even FEP have different intracranial hemodynamics compared to the healthy population (Owega et al 1998, Lee et al 2008, Lee et al 1999, but the results are overall inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleus accumbens together with the thalamus thus become a gateway for the dopamine signal that maintains an excessive cortical level of dopamine, and by stimulating DRD1 increases the secretion of dopamine in the brain’s lower-level structures, including the basal ganglia [ 54 ]. In the acute psychotic episodes, it was demonstrated by transcranial sonography, the increase of CBF and the velocity of blood flow from the posterior pole to the anterior pole, at the level of the Willis polygon, but also in other cerebral areas [ 55 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The variability and intensity of symptoms is dependent on the cerebellar vascular factor and suggest a CBF dysfunction in the posterior vascular territory and a possible alteration of the circulation speed in circle of Willis, unable to ensure the compensation by increase in the blood flow. From the diagnosis point of view, the transcranial echography and echography evaluation of fetal CBF may show a global decrease of the blood circulation speed in circle of Willis (Owega et al, 1998). The decrease in the cerebellar flow in the anterior pole (Figure 6a) is associated with HS while a a decrease in the posterior pole (Figure 6b, 6c) is correlated with anomalies in the CCTCC circuit.…”
Section: Cerebellar Dysfunctionmentioning
confidence: 99%